2022
DOI: 10.1016/j.ijrobp.2022.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic ACE-Inhibition Mitigates Radiation-Induced Pneumonitis by Suppressing ACE-Expressing Lung Myeloid Cells

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In addition to mediating an improved survival after hematopoietic injury, we observed that DIZE treatment also mitigated late morbidities due to pulmonary and renal failure. After 13.5 Gy PBI, rats in this model manifest morbidity from radiation pneumonitis characterized by rapid respiration (25). Here, we observed DIZE treatment reduces pneumonitis related morbidities and mitigates the increase in respiration rate at day 70 after PBI seen in irradiated control rats.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In addition to mediating an improved survival after hematopoietic injury, we observed that DIZE treatment also mitigated late morbidities due to pulmonary and renal failure. After 13.5 Gy PBI, rats in this model manifest morbidity from radiation pneumonitis characterized by rapid respiration (25). Here, we observed DIZE treatment reduces pneumonitis related morbidities and mitigates the increase in respiration rate at day 70 after PBI seen in irradiated control rats.…”
Section: Discussionsupporting
confidence: 50%
“…For example, ACE inhibitors have been shown to increase survival during H-ARS in rodent and pig models (1,43,44). Additionally, extensive studies by our group in the rat PBI model have demonstrated ACE inhibitors mitigate lung and kidney DEARE (8,25,28). It is possible ACE2 agonism may be acting to negate downstream ACE signaling by reducing the available amount of Angiotensin II (Ang II) to bind and activate Angiotensin II type 1 receptor (AT1R).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs like angiotensin-converting enzyme (ACE) inhibitors, which block elements that contribute to hypertension as their primary mechanism of action, were shown to reduce lethality associated with radiation exposure (both hematopoietic, 39 and from late lung complications). 40 , 41 It is conceivable that this product could also find use in the mitigation of certain chemical-induced lung complications. Still other products in advanced development for radiation-induced dermal 42 or lung 43 indications could be considered for potential use in an SM exposure scenario, and those under study for SM could be applied to the radiation space.…”
Section: Current Crn Environmentmentioning
confidence: 99%
“…However, there is inadequate evidence to conclude its effect on mortality and long-term outcomes in RP patients. 6,7 Amifostine is another widely studied pharmacological antioxidant reported to reduce RP when administered daily prior to RT. However, further studies have not confirmed this finding, and hence not recommended.…”
Section: Introductionmentioning
confidence: 99%